Epilepsy surgery in children with drug‐resistant epilepsy, a long‐term follow‐up. (7th June 2013) - Hallböök, T.; Tideman, P.; Rosén, I.; Lundgren, J.; Tideman, E.
Abstract : Objectives: In this follow‐up study, we wanted to present the long‐term outcome (5–21 years) in terms of seizure freedom, seizure reduction, and the cognitive development in the first 47 children who underwent epilepsy surgery at the University Hospital in Lund from 1991 to 2007. Materials and methods: All children who underwent epilepsy surgery in the southern region of Sweden were assessed for cognitive function before surgery and at follow‐up. A review of medical documents for demographic data and seizure‐related characteristics was made by retrospectively examining the clinical records. Results: Forty‐seven children with a median age at surgery of 8 years (range 0.5–18.7 years) were included. Twenty‐three children achieved seizure freedom, six demonstrated >75% improvement in seizure frequency, and none of the children experienced an increase in seizure frequency. Twenty‐one children required a reoperation to achieve satisfactory seizure outcomes. Cognitive functional level was preserved, and the majority of patients, 34 (76%), followed their expected cognitive trajectory. The patients who became seizure free significantly improved their cognitive processing speed, even after long‐term follow‐up. Conclusions: Epilepsy surgery in children offers suitable candidates a good chance of significantly improved outcome and low rates of complications. Several children, however, required a reoperation to achieve satisfactory seizure outcomes. Cognitive level was preserved, and the majority of patients followed their expected cognitive trajectory. Cognitive improvements in processing speed appear to occur in parallel with seizure control and were even more pronounced in subjects with no anti‐epilepsy drugs. These improvements persisted even after long‐term follow‐up.